2009
DOI: 10.3319/tao.2008.02.15.01(a)
|View full text |Cite
|
Sign up to set email alerts
|

Sorbent Tube Sampling and an Automated Thermal Desorption System for Halocarbon Analysis

Abstract: AB STRACTDe vel op ment and de ploy ment of the an a lyt i cal sys tem, ATD-GC-ECD has been es tab lished to mon i tor a suite of halogenated com pounds found in the at mo sphere at trace con cen tra tions. The in stru ment has been used to mon i tor ur ban back ground emis sion flux lev els in Bris tol, UK as well as Yel low stone Na tional Park, USA and an in door rain forest (Wild Walk@Bris tol, UK). The newly es tab lished sorbent tube sam pling sys tem is small and eas ily por ta ble and has been used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The trap on the ATD system was checked by running trap heat cycles, thereby establishing that the sample chromatograms were not affected by artefacts in the system. The multi-bed tubes exhibited no residual traces of any components at the analysis desorption temperature of 380 • C [19] precluding any sample carry-over between the consecutive runs. Previous studies have shown that traps containing Ascarite II do not alter the δ 13 C values obtained for CH 3 Cl.…”
Section: Determination Of δ 13 C Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The trap on the ATD system was checked by running trap heat cycles, thereby establishing that the sample chromatograms were not affected by artefacts in the system. The multi-bed tubes exhibited no residual traces of any components at the analysis desorption temperature of 380 • C [19] precluding any sample carry-over between the consecutive runs. Previous studies have shown that traps containing Ascarite II do not alter the δ 13 C values obtained for CH 3 Cl.…”
Section: Determination Of δ 13 C Valuesmentioning
confidence: 99%
“…In the present study, a preconcentration system suitable for large-volume sample collection was deployed in the Bristol urban area. [19] A new instrumental method is described that enables the application of Automated Thermal Desorber-Gas Chromatography-Combustion-Isotope Ratio Mass Spectrometry (ATD-GC-C-IRMS) to the isotope ratio measurement of selected halocarbons at ppt concentrations. Here we present δ 13 C values and mixing ratios of selected halocarbons from an urban background site in the city of Bristol, UK, generated using ATD-GC-C-IRMS and Adsorption Desorption System-Gas Chromatography-Electron Capture Detector (ADS-GC-ECD) systems in tandem.…”
Section: Introductionmentioning
confidence: 99%